The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1242/jcs.217554
|View full text |Cite
|
Sign up to set email alerts
|

Minimal in vitro systems shed light on cell polarity

Abstract: Cell polaritythe morphological and functional differentiation of cellular compartments in a directional manneris required for processes such as orientation of cell division, directed cellular growth and motility. How the interplay of components within the complexity of a cell leads to cell polarity is still heavily debated. In this Review, we focus on one specific aspect of cell polarity: the non-uniform accumulation of proteins on the cell membrane. In cells, this is achieved through reaction-diffusion and/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 204 publications
(266 reference statements)
0
23
0
Order By: Relevance
“…We found that motor-mediated protein clusters formed at microtubule ends were able to transfer to the walls, but non-clustered proteins were not.We further show that this transfer mechanism leads to preferential cluster accumulation at chamber poles, when microtubules are confined to elongated microfabricated chambers with sizes and shapes similar to S. pombe. may in principle be formed, either based on reaction-diffusion principles and/or dependent on cytoskeletal processes [Vendel et al 2019], but the exact mechanisms are not yet understood. Here we focus on the principles behind establishment of polarized protein distributions in the model system fission yeast, where dynamic microtubules are essential in targeting cell-end specific factors to the cell poles.…”
mentioning
confidence: 99%
“…We found that motor-mediated protein clusters formed at microtubule ends were able to transfer to the walls, but non-clustered proteins were not.We further show that this transfer mechanism leads to preferential cluster accumulation at chamber poles, when microtubules are confined to elongated microfabricated chambers with sizes and shapes similar to S. pombe. may in principle be formed, either based on reaction-diffusion principles and/or dependent on cytoskeletal processes [Vendel et al 2019], but the exact mechanisms are not yet understood. Here we focus on the principles behind establishment of polarized protein distributions in the model system fission yeast, where dynamic microtubules are essential in targeting cell-end specific factors to the cell poles.…”
mentioning
confidence: 99%
“…In recent years, several methods have been developed that offer novel means of reconstituting polarity in non-polar environments ( Table 1). Several approaches have also been developed for prokaryotic and simple eukaryotic yeast cells (Vendel et al, 2019). Here, I describe an "induced polarity" assay protocol used in cultured Drosophila S2 cells that utilizes the cell adhesion protein, Echinoid (Ed), to reconstitute cortical polarity in these otherwise non-polar cells (Figure 1; Johnston et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In the future, it would be interesting to study the shapedependent effects on other reaction-diffusion and cell-polarity inducing systems, such as Cdc42. 39 Equally, the effects on other cell division systems than FtsZ, e.g. MreB, or cellular signalling, could be elucidated.…”
Section: Discussionmentioning
confidence: 99%